Deafness and Sound in Small, Slow but Steady (2022) - Wang, Xinyi (Cultural Arts Research and Development, 2025)
This article focuses on the Japanese contemporary film Small, Slow but Steady and explores how deaf people experience sound physically, through the body. Among contemporary Japanese films that challenge ableist views of deafness, Small, Slow but Steady bridges the gap between hearing and deafness by portraying its deaf protagonist, Keiko, in relation to sound and bodily sensation. The film emphasizes her personal journey, illustrating how she engages with sound in a unique, embodied way. It often magnifies ordinary background noises, transforming them into heightened sensory moments that evoke emotional responses. Sound becomes a fluid boundary that highlights both the differences and interactions between hearing and deaf people. I adopt a phenomenological approach that emphasizes the perceptual qualities of sound. To be specific, I delve deep into film theories concerning sound, with particular attention to its material aspects—such as the concept of “haptic sound” as discussed by Laura Marks. Sound is portrayed as deeply intertwined with the senses of touch, sight, and taste. By manipulating sound to engage multiple senses—like touch, sight, and even taste—the film creates a deeply immersive experience. This integration of sound and tactile perception effectively conveys emotion and enhances the spectators’ affective engagement.